ANALISA METODE INVERSI IMPEDANSI AKUSTIK UNTUK IDENTIFIKASI RESERVOAR PADA FORMASI PLOVER DI LAPANGAN âQAIMAUâ BONAPARTE BASIN TIMOR SEA TIMOR-LESTE - , MOISES SOARES; , Sudiartono,S.U.,Drs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It has been carried out an analysis of acoustic impedance inversion with model -based method to identify reservoir rocks ( sandstone ) at Plover formations Bonaparte basin in ' Qaimau ' field. The Plover Formation is a formation that contains gas sand lithology interbeded with shale lithology . The main data in seismic inversion are seismic data and wells as the control data . In this study use post - stack 2D seismic data, one well data and two horizons . The Horizon is the Top Plover Formation and Bottom Plover Formation . Based on the results of horizons are used to determine areas with high structure . While the results of log analysis are used to determine the value of acoustic impedance reservoir in ' Qaimau ' field. From the results of log analysis in Plover formations indicates that reservoir the low impedance value interpreted as sandstone while the high impedance interpreted as shale . From the results of the seismic inversion of acoustic impedance values obtained on the formation Plover reservoir is 31000-35000 ( ft / s ) * ( g / cc ) . Then to slice on the inversion results to determine the distribution of the reservoir based on the value of acoustic impedance are obtained . The prospect area as a reservoir in ' Qaimau ' field is an area that has low acoustic impedance value and a associated high structure.